Factors causing a decrease in tourism in the Acapulco coastal zone, Mexico, and subsequent effects. - Rivera-González, Oscar Daniel (2021)
The following article analyzes the decrease in national and international tourism along the Acapulco coastal zone, causing adversities for inhabitants who sustain their economy on said activity and its economic contribution. Currently, based on theoretical and empirical research, a considerable decrease in tourism activity has been evidenced. This finding is ratified and quantified based on formal interviews with residents and tourists that point to excessive and unregulated early-stage urban growth as one triggering causative factor as it increases the generation of municipal solid waste, pollution, insecurity, violence and many other negative consequences mentioned throughout the article. The inaction and indifference of the authorities, mainly that of the Municipal Government of Acapulco and the Government of the State of Guerrero, encourage the progression of the aforementioned damaging issues. In view of the above, urgent measures are proposed to counter the deceleration of tourism in the port of Acapulco, which are to be applied urgently and effectively, with main consideration of the population, since otherwise it will become a forgotten and scantly visited port in the near future.